2018
DOI: 10.1021/acsomega.7b01934
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Stress Alleviation by Selenium Nanoparticle Treatment in Grain Sorghum

Abstract: The role of selenium nanoparticles (Se-NPs) in the mitigation of high-temperature (HT) stress in crops is not known. The uptake, toxicity and physiological and biological effects of Se-NPs under HT were investigated in grain sorghum [ Sorghum bicolor (L.) Moench]. Se-NPs of size 10–40 nm were synthesized and characterized to indicate nanocrystalline structure. A toxicity assay showed that Se-NPs concentration inducing 50% cell mortality (TC50) was 275 mg L –1 . Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(92 citation statements)
references
References 56 publications
2
71
0
Order By: Relevance
“…The nSe compound also acted as an elicitor to stimulate secondary metabolism as it was indicated by induction in the activity of PAL enzyme (a vital enzyme in phenylpropanoid metabolism), up-regulation in expression of 4CL and PAL genes, as well as an increase in concentrations of soluble phenols. These results are in line with several recent reports [4,6,7,9,12]. In Fig 12, a schematic model on the possible nSe-associated mechanisms is depicted.…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…The nSe compound also acted as an elicitor to stimulate secondary metabolism as it was indicated by induction in the activity of PAL enzyme (a vital enzyme in phenylpropanoid metabolism), up-regulation in expression of 4CL and PAL genes, as well as an increase in concentrations of soluble phenols. These results are in line with several recent reports [4,6,7,9,12]. In Fig 12, a schematic model on the possible nSe-associated mechanisms is depicted.…”
Section: Plos Onesupporting
confidence: 90%
“…Selenium (Se) is a metalloid element considered to be a vital essential micronutrient in humans and many other living organisms [4,5]. However, its essentiality and function for plant species remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports confirmed that Se can stimulate the growth and plant quality at low applied concentration (Golubkina et al, 2018), improve the photosynthesis rate (Jiang et al, 2017amd Zsiros et al, 2019, and strengthen the plant defense under stress (Bocchini et al, 2018;Hawrylak-Nowak et al, 2018;Singh et al, 2018 andKolbert et al, 2019). On the other hand, nano -selenium (nano-Se) or selenium nanoparticles (Se-NPs) has also distinguished features including low toxicity and high bioactivity comparing with other Se-forms like selenate or selenite or selenomethionine (Djanaguiraman et al, 2018). In human and animal health, many applications have been reported also for nano-selenium including the nano-medicine and therapeutic applications (Chaudhary et al, 2016;Zhao et al, 2017;Hosnedlova et al, 2018;Khurana et al, 2019 andSong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was conducted in a completely randomized design. The mouse fibroblast L929 cell line was procured from ATCC, India, and used in MTT and DAPI assays with and without nanoceria as explained by Djanaguiraman et al 75 In the MTT assay, the cell viability was calculated as the ratio of optical density (OD) of the nanoceria-treated cells to OD of the control cells and expressed as percentage. For DAPI staining, the mouse fibroblast cell line was seeded in 96-well plates (5 × 10 3 cells per well) and cultured overnight to adhere on the well, after that different concentrations of nanoceria (0, 100, 250, and 500 mg L –1 ) were added and left for 48 h. After completion of the reaction, the fibroblast cells were washed and fixed using phosphate-buffered saline and 70% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…The collected soil fraction (<2 mm) was again sieved through a 1 mm sieve (sieve number 20), and the fraction that does not pass through sieve (very coarse sand) was collected and soaked in aqua regia (3:1 HCl/HNO 3 acid ratio, 10 mL per g of sand) for 1 day and then washed thoroughly four times with double distilled water. Then, the soil was air-dried for 48 h and used for nanoceria uptake study as described by Djanaguiraman et al 75 In brief, the sorghum var. CO 30 was sown and grown in acid-washed sand by irrigating with one-quarter-strength Hoagland solution till 2 weeks.…”
Section: Methodsmentioning
confidence: 99%